Pancreatic β‐cell imaging in humans: fiction or option?. Issue 1 (5th October 2015) - Laurent, D.; Vinet, L.; Lamprianou, S.; Daval, M.; Filhoulaud, G.; Ktorza, A.; Wang, H.; Sewing, S.; Juretschke, H.‐P.; Glombik, H.; Meda, P.; Boisgard, R.; et al.
Abstract : Diabetes mellitus is a growing worldwide epidemic disease, currently affecting 1 in 12 adults. Treatment of disease complications typically consumes ∼10% of healthcare budgets in developed societies. Whilst immune‐mediated destruction of insulin‐secreting pancreatic β cells is responsible for Type 1 diabetes, both the loss and dysfunction of these cells underly the more prevalent Type 2 diabetes. The establishment of robust drug development programmes aimed at β‐cell restoration is still hampered by the absence of means to measure β‐cell mass prospectively in vivo, an approach which would provide new opportunities for understanding disease mechanisms and ultimately assigning personalized treatments. In the present review, we describe the progress towards this goal achieved by the Innovative Medicines Initiative in Diabetes, a collaborative public–private consortium supported by the European Commission and by dedicated resources of pharmaceutical companies. We compare several of the available imaging methods and molecular targets and provide suggestions as to the likeliest to lead to tractable approaches. Furthermore, we discuss the simultaneous development of animal models that can be used to measure subtle changes in β‐cell mass, a prerequisite for validating the clinical potential of the different imaging tracers.